Addictive disorders in Arctic climates : theory, research, and practice at the Novosibirsk Institute - Segal, Bernard (Routledge, 2013)
Discover fresh perspectives on alcoholism treatment and research with this enlightening new book describing the work of researchers at the Novosibirsk Medical Institute, USSR. By using specific examples of their studies in Siberia, the researchers offer an innovative approach to the treatment of addictive disorders in general. Instead of focusing on the drinking behavior itself, the treatment focuses on the relation of the problem to the interaction of economic, social, and psychological factors. To address the question of whether alcoholics should all be treated in the same way, or.